The Shared and Specific Genes and a Comparative Genomics Analysis within Three Hanseniaspora Strains. (2nd June 2019) - Chen, Kai; Tian, Zhonghuan; Jiang, Fatang; Cheng, Yunjiang; Long, Chao-an
Abstract : Kloeckera apiculata plays an important role in the inhibition of citrus postharvest blue and green mould diseases. This study was based on the previous genome sequencing of K. apiculata strain 34-9. After homologous comparison, scaffold 27 was defined as the mitochondrial (mt) sequence of K. apiculata 34-9. The comparison showed a high level of sequence identity between scaffold 27 and the known mtDNA of Hanseniaspora uvarum . The genome sequence of H. vineae T02/19AF showed several short and discontinuous fragments homologous to the mtDNA of H. uvarum . The shared and specific genes of K. apiculata, H. uvarum, and H. vineae were analysed by family using the TreeFam methodology. GO analysis was used to classify the shared and specific genes. Most of the gene families were classified into the functional categories of cellular component and metabolic processes. The whole-genome phylogram and genome synteny analysis showed that K. apiculata was more closely related to H. uvarum than to H. vineae . The genomic comparisons clearly displayed the locations of the homologous regions in each genome. This analysis could contribute to discovering the genomic similarities and differences within the genus Hanseniaspora . In addition, some regions were not collinearity-matched in the genome of K. apiculata compared with that of H. uvarum or H. vineae, and these sequences might have resulted from evolutionary variations.